The effects of self-efficacy promotion program toward the stoma skin care on self-care ability of patients and caregivers - kraisoda, kritsaya; Srimoragot, Pongsri; Wongkongkum, Kesiri (Thai Journal of Nursing, 2022)
This quasi-experimental research aimed at assessing the effects of self- efficacy promotion program toward the stoma skin care on self-care ability of patients and caregivers. The subjects were new patients who had been postoperative ostomy surgery and their caregivers at surgery department Udon Thani Hospital. A total of 52 colostomy patients and caregiver’s dyads were purposively selected into a control group (n = 26) and experimental group (n = 26). The control group received routine care only while the experimental group received routine care and the self-efficacy promotion program toward the stoma skin care. The program applied Bandura's Self-Efficacy Theory as the conceptual framework. Research instruments of patients and family caregivers consisted of the self- efficacy promotion program, the stoma skin care skill, and self-care ability of the stoma skin. Data were analyzed using descriptive statistics, Chi-square test, t-test, and Mix repeated measure ANOVA. Results: The experimental group's post-intervention stoma skin care skill and self-care ability were significantly higher than its pre-intervention score (p < .01), and significantly higher than that of the control group (p < .01).